KETERAMPILAN MENGELOLA KELAS DALAM MENINGKATKAN KEDISIPLINAN SISWA - Muhammad Nur; Siti Mariyah; Samsir (STAI Miftahul Ulum Tanjungpinang, 2023)
This study aims to improve the discipline of students at SDN 004 Mantang, Bintan. Initially the level of student discipline can be said to be still lacking. Class management skills are an activity carried out by teachers for their students in the classroom in an effort to regulate all learning components so that they can run well. The results of this study indicate that the application of classroom management skills in improving student discipline at SDN 004 Mantang-Bintan. it can be concluded from the results of processed data through measurement techniques with a Likert scale, in this case it can be concluded that the application of classroom management skills in improving student discipline at SDN 004 Mantang – Bintan is categorized as good with a percentage level of 73.01%. conducting teaching and learning activities often pay attention and direct students to obey and obey the rules before starting to provide learning materials.